Evaluasi Kinerja Crushing Plant Menggunakan Metode OEE dan Hubungannya dengan Production Rate Index (PRI) di PT Gunung Lagadar Abadi, Kecamatan Margaasih, Kabupaten Bandung, Provinsi Jawa Barat - Firman Firdaus Has; Solihin; Rully Nurhasan Ramadani (Bandung Conference Series: Mining Engineering, 2022)
Abstract. PT Gunung Lagadar Abadi has a problem with tools that are less effective in achieving production, in order to be able to streamline the performance of these tools, it is necessary to do an assessment of the problems, one of which is in the mining processing area where in a crushing plant unit there is a crusher consisting of 3 jaw primary crusher, secondary jaw crusher and tertiary cone crusher parts. The tool has continuity in a work system. At the primary crusher stage, the results obtained are Mechanical Availability (MA) 96.64%, Physical Availability (PA) 96.78%, Use of Availability (UA) 95.69%, Effective of Utilization (EU) 92.61%, and Production rate index (PRI) 35.10%. Furthermore, in the secondary crusher stage, the results obtained are Mechanical Availability (MA) 97.64%, Physical Availability (PA) 97.75%, Use of Availability (UA) 95.15%, Effective of Utilization (EU) 93.01%, and Production rate index (PRI) 93.56%. In the last stage of tertiary crushing, the results obtained are Mechanical Availability (MA) 98.64%, Physical Availability (PA) 98.66%, Use of Availability (UA) 98.55%, Effective of Utilization (EU) 97.23% and Production rate index (PRI) 33.35%, and the resulting OEE 49.29%. Based on the calculation results of the overall equipment effectiveness (OEE) value, which is 49.29%, it can be diagnosed that the overall equipment working on the crushing plant unit is not effective because it is far from an acceptable benchmark value of 85%, there are three components (availability, performance, rate of quality product) which is the biggest problem, one of which is the rate of quality product which is less than 85% so that the resulting production rate index (PRI) is small because the mechanical equipment to produce production does not work in accordance with its capacity, which at least works up to 85%, meanwhile the availability parameter is not a problem because the resulting value is more than 95% as well as the performance parameter. Abstrak. PT Gunung Lagadar Abadi memiliki permasalahan alat yang kurang efektif dalam mencapai produksi, guna untuk dapat mengefektifkan kinerja alat tersebut, perlu dilakukannya pengkajian terhadap permasalahan – permasalahan yang salah satunya berada pada area pengolahan tambang dimana pada suatu unit crushing plant terdapat alat peremuk yang terdiri dari 3 bagian jaw primary crusher, jaw secondary crusher dan tertiary cone crusher. Alat tersebut memiliki kesinambungan dalam suatu sistem kerja. Pada tahap primary crusher diperoleh hasil Mechanical Availability (MA) 96,64%, Phyisical Availability (PA) 96,78%, Use of Availability (UA) 95,69%, Effective of Utilization (EU) 92,61%, dan Production rate index (PRI) 35,10%. Selanjutnya pada tahap secoundary crusher diperolah hasil Mechanical Availability(MA) 97,64%, Phyisical Availability (PA) 97,75%, Use of Availability (UA) 95,15%, Effective of Utilization (EU) 93,01%, dan Production rate index (PRI) 93,56%. Pada tahap terakhir tertiary crushing diperoleh hasil Mechanical Availability (MA) 98,64%, Phyisical Availability (PA) 98,66%, Use of Availability (UA) 98,55%, Effective of Utilization (EU) 97,23% danProduction rate index (PRI) 33,35%, dan OEE yang dihasilkan 49,29%. Berdasarkan hasil perhitungan nilai overall equipment effectiveness (OEE) yaitu sebesar 49,29%, sehingga dapat didiagnosa bahwa keseluruhan alat yang bekerja pada unit crushing plant tidak efektif dikarenakan jauh dari nilai standar yang dapat diterima yaitu sebesar 85%, terdapat tiga komponen (availability, performance, rate ofe quality product) yang menjadi permasalahan tersebesar salah satunya pada rate ofe quality product yang kurang dari 85% sehinga nilai production rate index (PRI) yang dihasilkan kecil karena alat mekanis untuk menghasilkan produksi tidak bekerja sesuai dengan kapasitasnya yang setidaknya alat bekerja mencapai 85%, sementara itu parameter availability tidak menjadi permasalahan dikarenakan nilai yang dihasilkan lebih dari 95% begitu pula dengan parameter performance.